Development of Magnesium and Siloxane-Containing Vaterite and Its Composite Materials for Bone Regeneration - Yamada, Shinya; Obata, Akiko; Maeda, Hirotaka; Ota, Yoshio; Kasuga, Toshihiro (Frontiers in Bioengineering and Biotechnology, 2015)
Development of novel biomaterials with Mg2+, Ca2+ and silicate ions releasability for bone regeneration is now in progress. Several inorganic ions have been reported to stimulate bone-forming cells. We featured Ca2+, silicate and especially Mg2+ ions as growth factors for osteoblasts. Various biomaterials, such as ceramic powders and organic-inorganic composites, releasing the ions have been developed and investigated in their cytocompatibilities in our previous work. Through the investigation, providing the three ions was found to be effective to activate osteogenic cells. Mg and siloxane-containing vaterite (MgSiV) was prepared by a carbonation process as an inorganic particles, which can provide simultaneously releasing ability of Ca2+, silicate and Mg2+ ions to biodegradable polymers. Poly(L-lactic acid) (PLLA)- and bioactive PLLA-based composites containing vaterite coatings were discussed on their degradability and cytocompatibility using a metallic Mg substrate as Mg2+ ion source. PLLA/SiV composite film, which has a releasability of silicate ions besides Ca2+ ion, was coated on a pure Mg substrate to be compared with the PLLA/V coating. The degradability and releasability of inorganic ions were morphologically and quantitatively monitored in a cell culture medium. The bonding strength between the coatings and Mg substrates was one of the key factors to control Mg2+ ion release from the substrates. The cell culture tests were conducted using mouse osteoblast-like cells (MC3T3-E1 cells); cellular morphology, proliferation and differentiation on the materials were evaluated. The PLLA/V and PLLA/SiV coatings on Mg substrates were found to enhance the proliferation; especially the PLLA/SiV coating possessed a higher ability of inducing the osteogenic differentiation of the cells.